A Study on the Mechanisms of Interaction between Deep Foundation Pits and the Pile Foundations of Adjacent Skewed Arches as well as Methods for Deformation Control. (17th April 2018) - Cui, Kai; Feng, Jun; Zhu, Chengyong
Abstract : The construction of deep foundation pits is characterized by heavy loads on pile foundations, complex interactions between the foundation pit and pile foundations, and stringent requirements for deformation control. In this work, FLAC3D was used to perform computational analyses on the displacement responses of pile caps and the retaining walls of foundation pits in a variety of cases and reinforcement schemes. The computational results indicate that the piles of skewed arches interact with the retaining walls of the foundation pits through soil masses. We also revealed the mechanism by which deep foundation pits interacted with the pile foundations of adjacent skewed arches. Based on the mechanisms of interaction between foundation pit excavations and the piles of skewed arches, we proposed three reinforcement schemes for controlling the deformations associated with these interactions. The arched wall reinforcement scheme could provide a satisfactory result in terms of the control of horizontal displacements in the pile foundations and project costs.